2014
DOI: 10.1080/13607863.2014.962008
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning from caregiver to visitor in a long-term care facility: the experience of caregivers of people with dementia

Abstract: The findings offer insight into the experiences felt by caregivers when their relative or friend with dementia is admitted to hospital. Implications of this study include the need to improve the transition process for the caregiver by allowing them to be involved in the decision-making process, keeping them informed of care decisions, and importantly, providing emotional support to help the caregiver positively adapt to this transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(79 citation statements)
references
References 24 publications
3
76
0
Order By: Relevance
“…Still, family members that visit nursing homes may have negative experiences of grief and loneliness (Crawford et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Still, family members that visit nursing homes may have negative experiences of grief and loneliness (Crawford et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Previous literature has consistently reported the impact of admitting a person with dementia to a RAC facility on family caregivers (e.g. Bramble, Moyle, & McAllister, ; Crawford et al, ; Schulz et al, ). Staff were highly aware of the needs of family members during this period, and attempted to provide support, encouragement and assistance during the transition period, which was appreciated by families.…”
Section: Discussionmentioning
confidence: 99%
“…Toot, Swinson, Devine, & Challis, ), and the experience of the relocation for family carers of people with dementia (e.g. Crawford, Digby, Bloomer, Tan, & Williams, ; Schultz, Belle, & Czaja, ). There are also multiple studies determining how older adults in general settle in or adjust to their new environment during the early months (for reviews, see Brownie, Horstmanshof, & Garbutt, ; Fitzpatrick & Tzouvaka, ).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of certain factors as families adapt to institutionalization, such as the senior’s involvement in making said decision, professional support during decision-making, agreement from other family members and society, as well as aspects related to satisfaction with the nursing home’s function and interaction and collaboration with the formal care system [ 21 , 22 , 23 ], has been pointed out. However, little effort has been made to include these factors in a theoretical model to help us better understand the family adjustment process.…”
Section: Introductionmentioning
confidence: 99%
“…The research conducted on the psychological consequences concerning the institutionalization of an older adult in the family has shown that, after their admission, the family keeps on assuming the difficulties related to the older adult’s health problems, in addition to the problems faced during the above decision-making and changes in circumstances. In this regard, it is worth mentioning the different research lines associated with identifying the psychological implications of institutionalization within the family [ 22 ], presence of risk factors for admission and subsequent adaptation [ 21 ], or development of programmes aimed at incorporating relatives in the formal care system [ 24 ]. Nonetheless, for this knowledge area to further develop, measures aimed at properly assessing family adjustment to the older adult’s institutionalization are needed.…”
Section: Introductionmentioning
confidence: 99%